A Study on Relationship between Data Mining and Big Data - Srivastava, Kavita (International Journal of Computer Sciences and Engineering, 2019)
Big data is an expression for a data set. Big data sets are those that exceed the straightforward sort of database and data taking care of models that were utilized in before times, when big data was progressively costly and less achievable. Experts also initiate the distinctiveness and function of several popular running platforms. In this paper, we elaborate to identify the challenges and issues of big data and data Ming with closed relationship. We recognized quite a lot of factors from the big data and data Ming perspective and we also decorated the data Ming issue that justify considerable additional research and development. However, database and data taking care of models issues there a crucial difficulty for user to get used to into data Mining.